IIUM Kuantan Campus COVID-19 Guidelines - Mohammad Aidid, Edre; Rostam, Muhamad Ashraf; Muhamad Halil, Mohd Haikal; Adnan, Mohamad Syazwan; Ismail, Mohd Faisal; Zainal abidin, Norrul Afzan; Abd Karim, Noorzihan; Ghazali, Mohd Ariffin; Ahayalimudin, Nurul'Ain (IIUM Kuantan COVID-19 Operation Room, 2022)
COVID-19 has brought substantial morbidity and mortality to the world, Malaysia and the state of Pahang. The recent surge in the number of brought-in-dead cases and overburdened healthcare has made the condition worse. The current spread of the variant of concern, the delta variant, has become a threat to the campus. Thus, the IIUM Kuantan Campus Operation Room (OpRoom) has been continued in service since the previous tenure. The main function of OpRoom is to become the coordination centre of matters related to COVID-19 in IIUM Kuantan community and to communicate with Kuantan District Health Office on regular basis. With the establishment of Kulliyyah Taskforce (KTF), the handling of issues pertaining to COVID-19 can become smoother through the process of empowerment. This guideline is published to facilitate the management of COVID-19 in IIUM Kuantan Campus.